Metodologia para planejamento e análise de microrredes de estações de recargas rápidas considerando indicadores net zero energy building - Cruz, Matheus Souza da (2023)
The global goals defined for the reduction of the emission of Greenhouse Effect Gases (GHG) aiming to prevent the increase in the terrestrial temperature until the end of this century pass through the decarbonization of the transport sector, in view of its large participation in the emission of CO2. However, aiming at the dissemination of technology, several studies have been demonstrating that, in order to adhere to the so-called Electric Vehicles (EV), there is a need to create public infrastructures that allow fast charging of these, enabling displacements above their autonomies, and the Fast Charging Stations (FCS) on highways make up the largest portion of such infrastructure. Even if necessary, the development of FCS imposes challenges related to the high demands, and the integration of local microgeneration with or without storage can be considered, originating Microgrid topologies. In this context, the Net Zero Energy Building (NZEB) concept can contribute to the smart and sustainable development of FCS on highways through their energy planning. Thus, this work defines a methodology for the planning and analysis of FCS Microgrids considering the NZEB through quantitative indicators, allowing to optimize self-sufficiency and limit the impacts on the main electrical grid of the distributor. The methodology is applied to a real case study that considers the growth of EVs in southern Brazil. The analyzes simplified that the dimensioned Microgrid meets the energy needs of the FCS and presents the best NZEB indicators in the considered study horizon. Furthermore, the characterization of representative profiles for different load and generation conditions complements the analyses, demonstrating that the inclusion of storage promotes delay and reduction of the power flow reversal peak, in addition to further improving the NZEB indicators. Finally, the developed methodology demonstrates the importance of considering different scenarios in the planning of FCS Microgrids on highways that tend to grow in the coming years.